ANALISIS KEPUASAN PELANGGAN BUS PO. HARYANTO MOTORS INDONESIA - Athok, Mahmud Al; Budiwinarto, Kim (Universitas Of Surakarta, 2023)
This study aims to determine the expectations and reality felt by bus passengers of PO. Haryanto Motors Indonesia and knowing the satisfaction of bus passengers of PO. Haryanto Motors Indonesia while using it on a trip out of town. Customer satisfaction is measured by the difference in comparison between expectations (X) and reality (Y) using indicators of tangible, responsiveness, reliability, assurance, and empathy. This research is a quantitative case study. Secondary data was obtained from the company. The research population is part of the bus passengers PO. Haryanto Motors Indonesia. The number of samples in this study was 100 respondents. The analytical technique used is descriptive analysis, paired t-test, and grafics. The results showed that there was a significant difference between the expectations (X) of passengers and the reality (Y) felt by bus passengers PO. Haryanto Motors Indonesia.